Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi

Norges forskningsinnsats i Antarktis 2013-2022 - Forskningsrådet; Divisjon for energi, ressurser og miljø (Norges forskningsråd, 2012)
Keywords: Antarktis; Dronning Maud Land; forskning

Antarctic Treaty: Report of the Norwegian antarctic inspection under article VII of the Antarctic Treaty ([Justis- og beredskapsdepartementet], 2001)
Article VII of the Antarctic Treaty entitles each Consultative Party to designate observers who shall have the right to carry out unannounced on-spot inspections. The purpose of these inspections is to promote the objectives of and ensure compliance with the provisions of the Antarctic Treaty and the easures adopted under it. The observers shall be accorded complete freedom of access at any time to all areas of Antarctica, including all stations within those areas, as well as vessels and aircrafts at points of embarkation and disembarkation. Article 14 of the Protocol on Environmental Protection to the Antarctic Treaty commit the Consultative Parties to undertake inspections under Article VII of the Antarctic Treaty in order to promote the protection of the Antarctic environment and dependent and associated ecosystems, and to ensure compliance with the Environmental Protocol.
Keywords: Antarktis; Norge; forskningsstasjoner

The final report of the Fridtjof Nansen Institute on the International Antarctic Regime Project (Fridtjof Nansens institutt, 1995)
Keywords: Antarktis; forskning

The legitimacy of the Convention on the on the Regulation of Antarctic Mineral Resource Activities - Joyner, Christopher C (Fridtjof Nansens institutt, 1994)
Keywords: Antarktis; jus; mineraler

The protocol on environmental protection to the Antarctic Treaty: the question of effectiveness - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1994)
Keywords: Antarktis; jus; miljøvern

Executive summary: International Antarctic Regime Project publication series 1993 (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; litteratur; politikk

The regulation of Antarctic tourism: a study in regime effectiveness - Herr, Richard A; Davis, Bruce W (Fridtjof Nansen institutt, 1993)
Keywords: Antarktis; forvaltning; turisme

Chilean Antarctic policy: the influence of domestic and foreign policy - Infante, Maria Teresa (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; politikk

The effectiveness of the Convention on the Conservation of Antarctic Marine Living Resources - Stokke, Olav Schram (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; miljøvern

The Antarctic Treaty System and Antarctic tourism: towards a legal regime? (background information paper) - Vidas, Davor (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; politikk; turisme

The Antarctic Treaty System and the law of the sea: a new dimension introduced by the 1991 Madrid protocol - Vidas, Davor (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus

Executive summary: November 1992 (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; litteratur; politikk

ATS decision-making and change: the role of domestic politics in Australia - Davis, Bruce W; Herr, Richard A (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; politikk

The climate of Halley, Antarctica - Hanssen-Bauer, Inger; DNMI (Det norske meteorologiske institutt, 1992)
Keywords: Antarktis; klima; meteorologi

Antarctica and non-state actors: the question of legitimacy - Herr, Richard A; Davis, Bruce W (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; politikk

The role of domestic politics in making United States Antarctic policy - Joyner, Christopher C (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; politikk

The protection of the Antarctic environment - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; miljøvern

Domestic politics and non-state actors in the Antarctic Treaty System: towards a framework - Stokke, Olav Schram (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; politikk

Antarctic tourism: a challenge to the legitimacy of the Antarctic Treaty System? - Vidas, Davor (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; turisme

Veien til CRAMRA: en studie av forhandlingene om opprettelsen av et mineralregime i Antarktis - Mørkved, Berit (Fridtjof Nansens institutt, 1990)
Keywords: Antarktis; forvaltning; mineraler; politikk

Forholdet mellom vitenskap og politikk i internasjonal ressursforvaltning: det internasjonale samarbeid om forvaltning av de levende marine ressurser i Antarktis - Indreeide, Thor Vidar (Fridtjof Nansens institutt, 1989)
Keywords: Antarktis; Sørishavet; forskning; forvaltning; politikk; ressurser

Ressursforvaltningen i Antarktis - konflikt eller samarbeid? - Antonsen, Per (Fridtjof Nansens institutt, 1984)
Keywords: Antarktis; forvaltning; jus; ressurser

Norwegian Antarctic research : selected references - Orheim, Olav ([s.n.], 1984)
Keywords: Antarktis; bibliografi; polarforskning

Naturressurser i Antarktis: av særlig interesse for Norge - Mobæk, Are; Østgård, Jon; Børset, Erik; Karlsen, Bernt Stilluf; Larsen, Thor (Miljøverndepartementet, 1979)
Keywords: Antarktis; polarområdene; ressurser

Trends and prospects for regimes for living and mineral resources in Antarctica - Sollie, Finn (Stiftelsen, 1979)
Keywords: Antarktis; politikk; ressurser

Antarktis-traktaten, ressursene og utnyttelsen - Sollie, Finn (Stiftelsen, 1977)
Keywords: Antarktis; jus; politikk; ressurser

Norges ansvar i Antarktis - Sollie, Finn (Stiftelsen, 1977)
Keywords: Antarktis; politikk; ressurser

Vitenskapelig utforskning som internasjonalt samarbeidsprosjekt i polarområdene - Skagestad, Odd Gunnar (Stiftelsen, 1974)
Keywords: Antarktis; forskning; jus; politikk

Virksomheten i Arktis og Antarktis - Gjelsvik, Tore ([Norsk Polarinstitutt], 1973)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; marinbiologi; polarforskning; politikk

The duration of the Antarctic treaty: an analysis of the amendment and revision procedures in a political perspective - Sollie, Finn (Stiftelsen, 1973)
Keywords: Antarktis; jus; politikk

Suverenitet og samarbeid: Antarktis i samarbeidets tegn - Hanevold, Truls (Fridtjof Nansen-Stiftelsen, 1971)
Keywords: Antarktis; jus; politikk

Report on attendance at the Second Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6 to 15 August, 1970 - Kent, L E (Geological Survey of South Africa, 1971)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Antarktistraktaten: en ny type internasjonal organisasjon - Engh, Ulf (Stiftelsen, 1970)
Keywords: Antarktis; jus; politikk

De konsultative møter under Antarktistraktaten - Hanevold, Truls (Stiftelsen, 1970)
Keywords: Antarktis; jus; politikk

Norway's Antarctic research activities: report to SCAR - Norsk Polarinstitutt; Polarinstitutt, Norsk (Norwegian Polar Institute)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; forskning; forvaltning